Implementasi Kebijakan Sekolah Orang Tua Hebat (SOTH) Guna Mendukung Percepatan Penurunan Stunting: Studi di Kecamatan Sukolilo Kota Surabaya Provinsi Jawa Timur - Yunda Kholifah Saputriani; Radjikan Radjikan; Supri Hartono (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This research was motivated by the urgent case of stunting toddlers in Indonesia, including in the city of Surabaya. This stunting has a very negative impact on the health and growth and development of toddlers. The East Java BKKBN initiated the Great Parent School program and collaborated with the local government to implement this policy in the community. Continuing, the Mayor of Surabaya has formulated the policy of Mayor Regulation Number 106 of 2023 concerning Schools for Great Parents to support the acceleration of reducing stunting cases in the City of Surabaya. Sukolilo District is part of Surabaya City, so Sukolilo District also implements this policy. This program focuses on education for parents in parenting their children well and correctly. In implementing the SOTH program in Sukolilo District, researchers found that this program had a big influence on reducing the number of stunting cases currently in Sukolilo District in 2023-May 2024. Support from the public and the Mayor of Surabaya is one of the supporting factors for the success of this program. And parents should always apply the parenting patterns they have been taught so that their children avoid stunting. In this research the researcher used the Mazmanian and Sebatier model of policy implementation theory to describe the implementation of the policy, and the researcher used a descriptive-qualitative research approach in his research